Criminal Policy In Countermeasures Criminal Acts Of Domestic Violence Stairs To Children - Sumartini Dewi; Juhari; Kastubi (International Journal of Educational Research & Social Sciences, 2022)
Children are a bounty that must be maintained and protected by parents, families, and countries. Children must also get welfare because children are the next generation of the nation. The violence that occurs in children makes a problem that must be taken and resolved seriously because it impacts the growth and development of children. One of them is child abuse that occurs in households involving people closest to the child. It is essential to know what factors are the background to the criminal acts of domestic violence against children and how illegal policies in tackling domestic violence against children. This research uses normative juridical types with descriptive-analytical research specifications using primary and secondary data sources and qualitative analysis methods. The settlement of domestic violence crimes needs to get special attention and provide protection to children as victims of domestic violence. The Criminal Code only regulates the crime of violence in general in the Criminal Code, there are weaknesses, and to overcome these weaknesses. The violence against children occurs due to low educational factors, unhealthy environments, economic factors, and parents who vent anger at children. Applying protection to children who experience domestic violence must be enforced to protect children, both by penal and non-penal efforts.